Using Inverse Finite Element Analysis to Obtain Passive Mechanical Behavior of Abdominal Wall - Simón-Allué, Raquel; Oberai, Assad; Calvo, Begoña (Jornada de Jóvenes Investigadores del I3A, 2023)
In this work we develop a methodology to characterize in vivo the passive mechanical behavior of abdominal muscle, using for that finite element simulations combined with inverse analysis and optimization algorithms. The knowledge of the mechanical response of the muscle is needed to determine the features of the mesh in cases of hernia surgery.